Effect of Fly Ash Fraction and Mixing Process Variables On Mechanical Properties of Polymer Composites - Achmad, Zainun; Ismail, A.E; Kamarudin, Kamarul-Azhar; AK, Kareem (International Journal of Integrated Engineering, 2022)
The development of material technology continues to be carried out to meet the needs of engineering materials which are increasing day by day and are environmentally friendly or green. In this study, the process of making epoxy resin composites with fly ash was carried out from the combustion process of a power plant. This study aims to determine the strength of the mechanical properties between the epoxy resin and fly ash weight fraction by stirring treatment in the mixing process using tensile, flexural, and impact tests, microscopic examination, FTIR, and X-RD analysis. The treatments were mixing epoxy resin and fly ash with a weight fraction of 10%, 20%, and 30%, stirring speeds of 100 rpm, 150 rpm, and 200 rpm, for 10 minutes, 20 minutes, and 30 minutes. The results showed that the F2S3T3 composite had a greater tensile strength of 31,94 MPa, while the other composites had a tensile strength above 22-30 MPa, and the lowest was 13,07 MPa in the F1S2T3 composite. The maximum modulus of elasticity is found in the F3S3T1 composite with a value of 11,12 MPa, and the lowest is found in the F1S2T3 composite at 2,06 MPa. The F3S2T2 composite has a maximum flexural strength of 33,32 MPa, and the lowest composite F2S2T1 is 17,40 MPa with a flexural modulus of 270,41 MPa. The maximum flexural modulus in the F1S1T1 composite with a value of 382,76 MPa with a flexural strength value of 28,82 MPa. The F2S1T2 composite has an impact energy of 6,94 Joules with an impact strength of 203,47 MPa, and there are 2 composites that have the same impact energy value of 5,20 Joules, namely F3S2T2, and F3S1T3. From SEM observations, the fracture surface of the composite has a concave and prominent surface, but a lot of dust is trapped so it affects the bond in the matrix and reinforcement.